Republic of Lithuania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2010)
In Lithuania, the case for complementing the on going fiscal adjustment with revenue measures is strong. In addition to supporting the adjustment, options to raise revenue need to be tailored to enhance growth and export competitiveness. International and empirical evidence suggest important scope for revenue-enhancing tax reforms in Lithuania. Lithuania is in a position to rebalance growth towards exports. Executive Directors suggest a broad tax reform strategy that could raise revenue and tax new revenue sources while supporting growth, competitiveness, and equity to substantially bolster revenues.